Pembelajaran Peduli Lingkungan Melalui WEB dalam Mengimplementasikan Sekolah Ramah Anak di PAUD Assalam Kota Bengkulu - Dwi Ismawati; Yenda Puspita; Debi S. Fuadi; Meli Afrodita; Dwi Lyna Sari; Lazfihma (Institut Agama Islam Negeri Madura, 2024)
The personality of really focusing on the climate is a work or activity to really focus on nature and forestall ecological harm, with the goal that the climate stays feasible. Youth youngsters gain from something concrete and afterward they can think fundamentally. Reinforcing the personality of really focusing on the climate for small kids can be applied in conventional training at school. The school climate is supposed to give ecological training and change conduct to turn out to be more worried about the climate. Learning media in schools is likewise made more imaginative so it can bring up kids' interest. This exploration means to decide the impact of WEB on working on the personality of really focusing on the climate. The exploration utilized quantitative strategies with pre-exploratory examination utilizing a one gathering pretest - posttest plan. The complete testing of respondents in class B1 was 12. Information assortment strategies utilized tests and perception. Information was dissected utilizing the Autonomous Example T-test. The exploration results show that Asymp.Sig (2-followed) has a worth of 0.000 < 0.05, so H0 is dismissed, and Ha is acknowledged, intending that there is a typical distinction between the pretest and posttest so it very well may be inferred that picking up utilizing WEB can work on the ecologically mindful person of youth.